EFFECTIVENESS OF JIGSAW COOPERATIVE LEARNING MODEL ON CLASS X MATHEMATICS LEARNING IN SMA NEGERI 1 MAKASSAR - Muhammad Basri (Universitas Negeri Makassar, 2013)
The effectiveness of jigsaw type cooperative learning model is described by description, the result of learning mathematics taught by applying jigsaw type cooperative learning model on the subject of quadratic equation is in high category, whereas conventional learning is in medium category. Furthermore, the result of mathematics learning taught by applying jigsaw type cooperative learning model on the subject of two-variable linear equation system is in the high category whereas conventional learning on the subject of the system of linear equations of two variables is in the medium category. Jigsaw type cooperative learning model on the subject of quadratic equation is more effective than student learning outcomes taught by using conventional learning, as well as Jigsaw type cooperative learning model on the subject system of two linear equations is more effective than student learning outcomes are taught by using learning Conventional.